214k views
1 vote
What is the simplified form of the following expression? Assume y=0 ^3 sqrt 12x^2/16y

What is the simplified form of the following expression? Assume y=0 ^3 sqrt 12x^2/16y-example-1

2 Answers

3 votes

Answer: choice D

Step-by-step explanation: took it on edge

User Kmcnamee
by
4.8k points
4 votes

For this case we must simplify the following expression:


\sqrt [3] {\frac {12x ^ 2} {16y}}

We rewrite the expression as:


\sqrt[3]{(4(3x^2))/(4(4y))}=\\\sqrt[3]{(4(3x^2))/(4(4y))}=\\\frac{\sqrt[3]{3x^2}}{\sqrt[3]{4y}}=

We multiply the numerator and denominator by:


(\sqrt[3]{4y})^2:\\\frac{\sqrt[3]{3x^2}*(\sqrt[3]{4y})^2}{\sqrt[3]{4y}*(\sqrt[3]{4y})^2}=

We use the rule of power
a ^ n * a ^ m = a ^ {n + m} in the denominator:


\frac{\sqrt[3]{3x^2}*(\sqrt[3]{4y})^2}{(\sqrt[3]{4y})^3}=\\\frac{\sqrt[3]{3x^2}*(\sqrt[3]{4y})^2}{4y}=

Move the exponent within the radical:


\frac{\sqrt[3]{3x^2}*(\sqrt[3]{16y^2}}{4y}=\\\frac{\sqrt[3]{3x^2}*(\sqrt[3]{2^3*(2y^2)}}{4y}=


\frac{2\sqrt[3]{3x^2}*(\sqrt[3]{(2y^2)}}{4y}=\\\frac{2\sqrt[3]{6x^2*y^2}}{4y}=


\frac{\sqrt[3]{6x^2*y^2}}{2y}

Answer:


\frac{\sqrt[3]{6x^2*y^2}}{2y}

User Nathan Feger
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.